Interaction between LMFP and NCMA and Its Effect on Blending Cathode-Based Cells - Jingyuan Liu; Si Chen; Dewen Kong; Meiyuan Wu; Haijing Liu (Energies, 2024)
Li-ion cells with a LiMnxFe1−xPO4 (LMFP) and LiNi1−x−y−zCoxMnyAlzO2 (NCMA) blending cathode show their benefits of lower cost and higher safety compared to barely NCMA cathode-based cells. However, the rate capability of LMFP material is relatively poor compared to NCMA or even LiFePO4, which is because of the low electronic conductivity of LMFP material and the 1D diffusion channel in its structure. This work discusses the effect on electrochemical performance when blends of various ratios of LMFP are used in an NCMA cathode, with data verified by a 5 Ah pouch cell. This work further investigated the interaction between NCMA and LMFP during charge/discharge. Combining results from experiment and simulation, it evidences that blending more LMFP does not always lead to worse discharge rate but reduces charge rate. Moreover, it is found that, in a constant current discharge/charge process, although the system is under continuous discharge/charge, LMFP works intermittently. This leads to different diffusion polarization states of LMFP in the discharge/charge process and further results in a difference in discharge/charge rate capability. Therefore, to improve rate capability, especially charging rate, using smaller-sized or doped LMFP to improve its diffusion coefficient is an optimized strategy.